Operator's manual for SHEBA powered tether balloon system - Lappen, Cara-Lyn, author (Colorado State University. Libraries, 1998)
The Surface Heat and Energy Budget of the Arctic (SHEBA) was an intensive field project which took place in the Arctic Ocean from October 1997 through October 1998. Its purpose was to measure as many facets of the Arctic environment as possible so that we would be able to better understand the interaction between the ice, atmosphere, and ocean and their interactions with global climate. One aspect of the atmospheric field component was launching tethered balloons to monitor the profiles of temperature, wind, pressure, and humidity, as well as examine the vertical structure of cloud droplet sizes and distributions. The tethered balloon that we used was one specially designed for use in freezing climates by SPEC Corporation in Boulder, Colorado. A special winch that was able to withstand Arctic temperature and weather became necessary when the testing of simple winch systems used in warmer climates failed under these extreme conditions. The purpose of this manual is to acquaint any new user to the powered tethered balloon system deployed at the Surface Heat and Energy Budget of the Arctic (SHEBA) ice camp. It includes a description of the preparations necessary to get ready for a launch, the mechanics of the actual launch, and an account of the proper procedure for taking down the equipment when finished. It will also include tips on how to minimize potential equipment failures, some trouble shooting, and some safety ideas. This manual is designed so that new operators can use the system with minimal previous training. At the end of this manual, the reader will find a quick checklist.
April 1998.
Keywords: Meteorology -- Arctic regions